Bahasa Inggris - St. Hartina; Fitria Ningsih, Anjelita; Sahraini (elstic : english language linguistics culture, 2024)
This research aimed to analyze the students’ difficulties and causes in writing descriptive text. It applied a descriptive qualitative research design. The subjects of the research are a class of students in a senior high school in Palopo, South Sulawesi, Indonesia. The data were collected through documentation, interview, and observation. Based on the results of this study, three general difficulties were found for students in writing descriptive text, including 1) difficult to follow the generic structure of descriptive text; 2) difficult to use the linguistic features, and 3) misuse of writing mechanics. These difficulties are caused by several factors, including 1) the students are less in writing practice, 2) lack of writing ideas, 3) lack of vocabulary mastery, 4) lack of motivation in learning English. It is suggested that writing descriptive text should be learned and taught intensively.